PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI ELASTISITAS BERBASIS VIRTUAL LAB PhET TERHADAP HASIL BELAJAR SISWA KELAS X - Nailufar, Adila; Arjo, Sugianto (Universitas Tadulako, 2022)
This study uses a pre-experimental design using a one group pretest – posttest which aims to see the effect of using a guided inquiry learning model based on the PhET virtual lab on the learning outcomes of class X students especially elasticity material. Class X MIA 2 students as the experimental class were treated with the guided inquiry learning model, while the X MIA 1 class as the control class used the conventional learning model. The samples were students of class X MIA 1 and X MIA 2, with 28 students respectively. The instrument used in this research is a written test in the form of multiple choice. The type of data used in this research is to find quantitative data in the form of student learning outcomes. The data analysis technique used the SPSS 25 program. The pretest mean score in the control class was 75,28 and the experiment class was 76,82. The result of testing the hypothesis that the value of so that was rejected and was accepted.